2018
DOI: 10.1038/s41598-018-31707-9
|View full text |Cite
|
Sign up to set email alerts
|

Pro inflammatory stimuli enhance the immunosuppressive functions of adipose mesenchymal stem cells-derived exosomes

Abstract: The predominant mechanism by which adipose mesenchymal stem cells (AMSCs) participate to tissue repair is through a paracrine activity and their communication with the inflammatory microenvironment is essential part of this process. This hypothesis has been strengthened by the recent discovery that stem cells release not only soluble factors but also extracellular vesicles, which elicit similar biological activity to the stem cells themselves. We demonstrated that the treatment with inflammatory cytokines incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
173
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(182 citation statements)
references
References 42 publications
9
173
0
Order By: Relevance
“…Our findings revealed that EVs produced by IFNγ‐primed ASCs are more effective than EVs produced by naïve ASCs in curbing the inflammatory response in isolated macrophages and in repaired tendons. These findings are supported by several independent reports indicating that inflammation‐stimulated stem cell EVs possess enhanced immunosuppressive functions, and improved therapeutic efficacy in treating inflammation‐related conditions . The priming effect has been reported to be associated with selective enrichment of certain regulatory miRNA cargos in primed EVs, such as let‐7b and miR‐146a, which are capable of modulating the macrophage inflammatory response .…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Our findings revealed that EVs produced by IFNγ‐primed ASCs are more effective than EVs produced by naïve ASCs in curbing the inflammatory response in isolated macrophages and in repaired tendons. These findings are supported by several independent reports indicating that inflammation‐stimulated stem cell EVs possess enhanced immunosuppressive functions, and improved therapeutic efficacy in treating inflammation‐related conditions . The priming effect has been reported to be associated with selective enrichment of certain regulatory miRNA cargos in primed EVs, such as let‐7b and miR‐146a, which are capable of modulating the macrophage inflammatory response .…”
Section: Discussionsupporting
confidence: 73%
“…Adipose‐derived stem cells (ASCs), which represent a similar type of adult stem cell, have been found to shift the phenotypic response of infiltrating macrophages from a default pro‐inflammatory M1 phenotype to an anti‐inflammatory and pro‐regenerative M2 phenotype, thereby facilitating tendon healing . While the underlying mechanisms remain elusive, extracellular vesicles (EVs) have been identified as one of primary paracrine effectors of ASCs . EVs are cell‐derived vesicles that mediate cell–cell communication by delivering various functional molecules (e.g., proteins, messenger RNAs [mRNAs], and microRNAs) to selective recipient cells .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…EV‐based therapies are emerging as promising alternatives to cell‐based therapies. Although ADSCs and ADSC‐derived EVs have demonstrated immunomodulatory properties,74 studies on adipose tissue‐derived BiNPs are lacking. Direct isolation of BiNPs from adipose tissue takes less time, costs less, and results in higher yields compared to isolation of cell culture‐derived EVs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, adult MSCs exhibit attractive immunomodulatory properties in degenerative diseases in animals [27]. This is the case of ASCs, a type of MSC, which in addition to the cellular and molecular traits of BM-MSC, exhibits robust immunosuppressive activity, mediated by induction of the production of Tregs [28] and the selective release of several types of growth factors [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%